2017
DOI: 10.18632/oncotarget.15663
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A affects radiosenstivity in cervical squamous cell carcinoma and predicts poor prognosis

Abstract: BackgroundDefinitive radiation therapy (RT) (with or without cisplatin-based chemotherapy) is one of the most effective treatments for cervical squamous cell carcinoma (CSCC), but efficacy is limited due to resistance. In the present study, we investigated the relationship between the expression of Aurora kinase A (Aurora-A, AURKA)and response to RT in patients with CSCC.MethodsThe expression of Aurora-A in biopsy specimens of untreated primary tumors in 129 Uyghur patients with CSCC was investigated immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(57 reference statements)
1
9
0
1
Order By: Relevance
“…AURKA is associated with centrosomal expansion, spindle and chromosomal instability, and its high expression promotes tumor cell proliferation and invasion (Zhang, Wang, Liu, Hua, & Xin, 2009). The researchers (Sun et al, 2015) (Ma et al, 2017) found that AURKA is related to the resistance of taxol and radiosensitivity. Currently, AUARK inhibitors are being explored as molecular‐targeted medicines for the treatment of cervical cancer (Gabrielli et al, 2015; Umene et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AURKA is associated with centrosomal expansion, spindle and chromosomal instability, and its high expression promotes tumor cell proliferation and invasion (Zhang, Wang, Liu, Hua, & Xin, 2009). The researchers (Sun et al, 2015) (Ma et al, 2017) found that AURKA is related to the resistance of taxol and radiosensitivity. Currently, AUARK inhibitors are being explored as molecular‐targeted medicines for the treatment of cervical cancer (Gabrielli et al, 2015; Umene et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that four key genes were involved in cell cycle, participating in tumorigenesis and tumor proliferation. AURKA has been studied in a wide range of human malignancies and is associated with poor prognosis in several malignancies, including cervical squamous cell carcinoma, hepatocellular carcinoma, and nonsmall cell lung carcinoma (Ma et al, ; Wang et al, ; Zheng et al, ). Besides, Yang et al, () reported that AURKA as a transactivating co‐factor in the induction of the c‐Myc oncoprotein in breast cancer stem cells (BCSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the correlation of tumor radioresistance with Aurora-A expression was also studied. Ma’ et al showed that Aurora-A affected radiosensitivity in cervical squamous cell carcinoma [31]. Venkataraman’ et al [32] showed that targeting Aurora Kinase A enhanced radiation sensitivity of atypical teratoid rhabdoid tumor cells.…”
Section: Discussionmentioning
confidence: 99%